Voicing God: Theological Injunction to economic issues - Dube, Zorodzai (Verbum et ecclesia, 2017)
Taking a socio-historical approach, this chapter traces history from World War II (WWII) and illustrates the various instances in which economics and politics intersect with theological themes. After WWII the dominant paradigm in theology tilted towards a moral economy by focusing on issues of fairness, justice and peace. This chapter argues that, in view of the triumph of global capitalism since 1989, the future and relevance of theology is located within spaces that provide ethical and moral influence towards fairness and justice, thus agreeing with the central message of Jesus of Nazareth.